Relationship between population growth and socialeconomic development in the age structure perspective (on the example of Vietnam) - Thi Minh Hoa Nguyen; Ngoc Thanh Pham; Tuan Anh Ha (RUDN journal of Sociology)
Today most countries experience significant changes in the age structure of population - a transition from the youth dominance (associated with high birth and death rates in the past) to aging (due to declining birth and death rates) [46]. The age structure plays an important role in the national economic development: a shortage of labor determines its slowdown, while an excess of the working-age population (the so-called “demographic dividend”) determines its acceleration [21; 25]. Numerous empirical studies of the relationship between the age structure and social-economic development have shown that the economically active population (15-64-year-olds) has a strong positive impact on the growth of GDP per capita, and what is more important is not the overall increase in numbers but positive changes in life expectancy, age structure, etc. The authors mention three mechanisms of the demographic impact on social-economic development: the impact on the labor market, the impact on savings and capital accumulation, the impact on education coverage and human capital. Vietnam ranks 15th in the world in terms of the population size and belongs to the group of countries with the “golden structure” of the population in terms of the share of the youth (69% of the working-age population aged 15-64) but also demonstrates aging trends [8] that are expected to reach their maximum by 2035 [5]. The Vietnamese government implements many measures to take advantage of the “golden period” (development of human resources, attraction of investments, creation of jobs), but the average economic growth rate of 6.21% for 2011-2020 did not allow Vietnam to leave the group of countries with low middle income [49] and high rates of aging [12; 15], which determines the need to study the relationship between population growth and social-economic development in the context of the age structure. The article is based on the data from the General Statistics Office of Vietnam, the 1989, 1999, 2009 and 2019 population censuses and other demographic materials and forecasts.